Spatio-Temporal Land Use/Land Cover Analysis of Murree using Remote Sensing and GIS - Kausar, Rukhsana; Baig , Siddique; Riaz, Iqra (Asian Journal of Agriculture and Rural Development, 2016)
Land use land cover (LULC) patterns are significantly effecting the urban/rural spaces in the encompassing areas. Murree being tourist resort is always under pressure of tourists from all over the country. The population increase in peak season of tourism in summer season and extreme winter, causes a tremendous growth and expansion of urban area of Murree. So a relic of blue pine forest and Chir pine forest is expected to undergo tremendous change and to undergo expansion or degradation depending upon the tourist’s behavior. The present study uses Multi-Temporal Landsat (TM and ETM+ for year 1998, 2003, 2005, 2010) images to detect LULC change in Murree due to the enhanced activities of ecotourism. Change detection of three tourist hotspots of Murree region including Murree Mall, Bhurban and Patriata was evaluated through Maximum Likelihood Classification (MLC) algorithm. The urban expansion has impacted the land use, as it has increased from 57.37% to 69.10%. Result indicates that the Built-up area have increased by 11.73%, reserve forest by 8.11% while grassland and dense natural forest decreases by 7.50 and 12.37 percent respectively. The results provided the better knowledge and understanding of former and current spatial dynamics of LULC change in Murree region along with its ecotourism hotspots.